Buoyancy‐Tilted Shear Layers and Coherent Structures in Hyperpycnal River Plume Plunging - H. Shi; M. E. Negretti; J. Chauchat; K. Blanckaert; U. Lemmin; D. A. Barry (Water Resources Research)
Abstract Shear layers and corresponding Kelvin Helmholtz‐type Coherent Structures (KHCS) can be generated by rivers discharging into laterally‐unconfined quiescent open water bodies (e.g., lakes). When the river discharge has a greater density than the receiving water due to temperature and/or suspended sediment, both the shear layers and KHCS will be influenced by the negative buoyancy of the plume and thus become highly three‐dimensional (3D). The present study uses a turbulence‐resolving Computational Fluid Dynamics model based on Large Eddy Simulation to simulate the nearshore flow fields of a hyperpycnal river plume entering an unconfined quiescent ambient. Shear layers are observed at both sides of the plume and their growth is suppressed by negative buoyancy arising from the greater density of the river plume. The plume‐ambient interface is tilted by the negative buoyancy and is transformed into a curved face. As a result, the shear layer is also tilted and shear‐induced vorticity progressively changes its direction from vertical near the water surface to transversal near the bottom. Tilted along with the shear layers, KHCS present unique 3D subsurface structures and create strongly mixed and curved “coherent structure regions” in transects. Quadrant analysis shows that the “Ejection” and “Sweep” events associated with KHCS dominate the local mass and momentum exchange between the plume and ambient water. At the plume‐ambient interface, the KHCS generate near‐periodic velocity fluctuations whose non‐dimensionalized frequency (Strouhal number) decreases with increasing local Richardson number.